Analysis of the S3 and S3′ subsite specificities of feline immunodeficiency virus (FIV) protease: Development of a broad-based protease inhibitor efficacious against FIV, SIV, and HIV in vitro and ex vivo - Lee, Taekyu (The National Academy of Sciences, 1998)
The S3 and S3′ subsite binding specificities of HIV and feline immunodeficiency virus proteases (FIV) proteases (PRs) have been explored by using C(2)-symmetric competitive inhibitors. The inhibitors evaluated contained (1S, 2R, 3R, 4S)-1,4-diamino-1,4-dibenzyl-2,3-diol as P1 and P1′ units, Val as P2 and P2′ residues, and a variety of amino acids at the P3 and P3′ positions. All inhibitors showed very high potency against HIV PR in vitro, and their K(i) values ranged between 1.1 and 2.6 nM. In contrast to the low restriction of P3 and P3′ residues observed in HIV PR, FIV PR exhibited strong preference for small hydrophobic groups at the S3 and S3′ subsites. Within this series, the most effective inhibitor against FIV PR contained Ala at P3 and P3′. Its K(i) of 41 nM was 415- and 170-fold lower than those of the inhibitors without the P3 and P3′ moieties or with the Phe at these positions, respectively. In addition, these compounds were tested against mutant FIV PRs, which contain amino acid substitutions corresponding to those in native HIV PR at homologous sites, and their efficacy of inhibition progressively increased up to 5-fold. The most potent FIV PR inhibitor was selected for examination of its effectiveness in tissue culture, and it was able to block nearly 100% of virus production in an acute infection at 1 μg/ml (1.1 μM) against HIV, FIV, and simian immunodeficiency virus. Furthermore, it was not toxic to cells, and even after 2 months of culture there was no sign of resistance development by virus. The findings suggest that inhibitors with small P3 residue may be efficacious against a broad range of HIV variants as well as interspecies PRs.